Extremely severe obstetric morbidity and its relationship to maternal and perinatal health indicators - Juan Antonio Suárez González; Alberto Carlo Tembo; Mario Gutiérrez Machado; Alexis Corrales Gutiérrez; Hector de la Paz Muñiz (Acta Médica del Centro, 2011)
Introduction: Extremely severe obstetric morbidity is defined as any serious complica tion that occurs during pregnancy, childbirth or postpartum, which jeopardizes the life of women and that requires immediate attention to prevent death. Objective: to characterize patients with extremely severe obstetric morbidity. Methods: a longitudinal descriptive prospective-retrospective study was carried out at the Mariana Grajales Gynecology and Obstetric University Hospital in Santa Clara from January 2007 to December 2009. For the collection of information, a questionnaire with the variables of interest was devised by means of a review of the individual medical records, interviews with patients and data provided by the statistics department of the hospital. Results: it was found that 135 patients had extremely severe obstetric morbidity in the study period. The main causes were related to hemorrhage (52.59%) and hypertensive disorders (50.37%). It is noted that dystocic delivery through cesarean section (64.44%) was an obstetric event related to extremely severe obstetric morbidity. There is a direct relationship between maternal and perinatal outcomes in this group of patients. The Intensive Care Unit was used in cases of extreme gravity, and four maternal deaths occurred in these three years. It means that a total of 169 years of potential life were lost for reasons associated with maternity; and the average years of life potentially lost by each woman was 42.25 years. Conclusions: During the study period, hemorrhage and hypertensive disorders were the main causes of extremely severe obstetric morbidity. There was an obvious direct relationship with perinatal outcomes in these cases, and with cesarean delivery and the use of Units Intensive Care. Four maternal deaths were reported in this triennium.